Economic Implications of Reducing Carbon Emissions from Energy Use and Industrial Processes in Brazil - Chen, Y.-H. Henry; Timilsina, Govinda R. (World Bank, Washington, DC, 2012)
The overall impacts on the Brazilian economy of reducing CO2 emissions from energy use and industrial processes can be assessed using a recursive dynamic general equilibrium model and a hypothetical carbon tax. The study projects that in 2040 under a business-as-usual scenario, CO2 emissions from energy use and industrial processes would be almost three times as high as in 2010 and would account for more than half of total national CO2 emissions. Current policy aims to reduce deforestation by 70 percent by 2017 and emissions intensity of the overall economy by 36-39 percent by 2020. If policy is implemented as planned and continued to 2040, CO2 emissions from energy use and industrial processes would not have to be cut until 2035 as reductions of emissions through controlling deforestation would be enough to meet emission targets. The study also finds evidence that supports the double dividend hypothesis: using revenue from a hypothetical carbon tax to finance a cut in labor income tax significantly lowers the gross domestic product impacts of the carbon tax. Using carbon tax revenue to subsidize wind power can effectively increase the output of wind power in the country, although the impact of the tax on gross domestic product would be somewhat increased.